Evaluasi Penggunaan Antibiotik Pada Pasien Bronkopneumonia Anak Di Ruang Perawatan Melati Rsud Mukomuko Tahun 2024 - Elsa Febria Mutiara; Ariesta Kirana Efmisa; Devahimer Harsep Rosi; Aivi Yola Dwiputri (Journal of Science and Clinical Pharmacy Research, 2026)
Bronchopneumonia is an inflammatory lung condition affecting one or more lobes, characterized by infiltrative patches caused by bacteria, viruses, fungi, and foreign substances. The purpose of this study was to obtain an overview and analysis of the appropriateness of antibiotic use. This was a descriptive observational study with a retrospective approach using secondary medical record data. The results for the description of antibiotic use were Seftriakson (53.4%), Sefotaksim (27.6%), and meropenem (19.0%). The results of the quality assessment using the Gyssens Method revealed that 1.7% of antibiotic prescriptions were in category III B, 19% in category IV A, and 79.3% in category 0. These data indicate that there is still irrational use of antibiotics. Assessed using the ATC/DDD methodology, resulting in a total of 25.57 DDD per 100 days. The calculation findings show the highest Defined Daily Dose (DDD) value for the antibiotic Seftriakson at 18.06 DDD per 100 days of hospitalization, while the lowest value was seen for Meropenem at 2.09 DDD per 100 days and Sefotaksim at 5.42 DDD per 100 days of hospitalization. Clinical parameters showed a P value > 0.05, with p = 0.88, indicating no statistically significant difference between antibiotic administration and leukocyte levels in pediatric bronchopneumonia patients in the Melati ward at Mukomuko Hospital in 2024.